1986
DOI: 10.1080/01688638608405184
|View full text |Cite
|
Sign up to set email alerts
|

Paired associate learning: Normative data for differences between high and low associate word pairs

Abstract: Wilson, Bacon, Kaszniak, and Fox (1982) suggest that the learning of low associate pairs on the Wechsler Memory Scale involves episodic memory alone while the learning of high associate pairs involves semantic memory as well. Tulving (1983) also comments that, whereas some information in episodic memory is relatively unorganized and access to its content tends to be deliberate and requiring conscious effort (e.g., low associate pairs), information in semantic memory is organized and access to its content is mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…Additionally, the inspection of the learning curves showed that the performances of the future normal subjects presented a ceiling effect (mean = 5.93/6) on the third trial of the related pairs, whereas this was not the case for unrelated pairs (mean = 3.28/4), despite markedly increased performances across trials. Therefore, these results reinforce the belief that the retrieval of the unrelated and related pairs of the WPAT may be subsumed by different types of memory functioning thought to correspond, respectively, to controlled and more automatic components of memory functioning [8,9]. Among the 4 measures introduced into the PCA, the one chosen to characterize immediate recall corresponded to the performances at the third trial, thereby highlighting the contrast between the related and unrelated pair scores; at this trial, the related pairs were almost completely successful, whereas the unrelated pairs, despite the learning benefits, seemed still to be difficult to retrieve.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Additionally, the inspection of the learning curves showed that the performances of the future normal subjects presented a ceiling effect (mean = 5.93/6) on the third trial of the related pairs, whereas this was not the case for unrelated pairs (mean = 3.28/4), despite markedly increased performances across trials. Therefore, these results reinforce the belief that the retrieval of the unrelated and related pairs of the WPAT may be subsumed by different types of memory functioning thought to correspond, respectively, to controlled and more automatic components of memory functioning [8,9]. Among the 4 measures introduced into the PCA, the one chosen to characterize immediate recall corresponded to the performances at the third trial, thereby highlighting the contrast between the related and unrelated pair scores; at this trial, the related pairs were almost completely successful, whereas the unrelated pairs, despite the learning benefits, seemed still to be difficult to retrieve.…”
Section: Discussionsupporting
confidence: 73%
“…The juxtaposition in the same test of unrelated and related associations has the advantage to provide a measure of two different mental activities: recall of well-established verbal associations and retention of new unfamiliar verbal associations [7]. In the light of the theoretical distinction between effortful and automatic processing, and depending on whether the to-be-remembered material makes use of existing associations in the memory network or not, two types of memory functioning were thought to be involved [8,9]. Therefore, it can be assumed that unrelated pairs which do not make use of old associated learning need a deliberate and sustained effort to be retrieved, and thus involve the more controlled aspects of memory functioning such as the strategic aspects of memory retrieval proposed by Moscovitch [10], whereas related pairs make us of well-learned associations, so their access involves more automatic components of memory functioning.…”
Section: Introductionmentioning
confidence: 99%
“…The score was the sum of pairs correctly recalled (maximum, 12). A neurologically normal Australian group obtained a mean of 7.45 on this task (21), whereas our previously studied group with left HS obtained a mean score of 3.6 points (22). Hard paired‐associate learning was included here because of its known sensitivity to left HS.…”
Section: Methods and Subjectsmentioning
confidence: 62%
“…However, in the light of our findings so far, the resemblance between the tip‐of‐the‐tongue rates of bilinguals and the elderly raises an intriguing question: Can learning account for age‐related memory differences, such as those observed in Paired‐Associate Learning (PAL; a psychometric measure of people's ability to learn and recall new information)? In PAL tests, such as the commonly used PAL subtest of Wechsler's Memory Scale (WMS; des Rosiers & Ivison, ), subjects learn pairings between word cues (e.g., baby; jury ) and word responses ( cries; eagle ) and have to supply the appropriate response to each cue at test. Although performance on individual items varies (Fig.…”
Section: Lexical Knowledge and Paired‐associate Learningmentioning
confidence: 99%